2008
DOI: 10.1099/jmm.0.47752-0
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni response to human mucin MUC2: modulation of colonization and pathogenicity determinants

Abstract: Campylobacter jejuni is the main cause of bacterial acute gastroenteritis worldwide. In its colonization of the host intestinal tract, it encounters secreted mucins in the mucus layer and surface mucins in the epithelial cells. Mucins are complex glycoproteins that comprise the major component of mucus and give mucus its viscous consistency. MUC2 is the most abundant secreted mucin in the human intestine; it is a major chemoattractant for C. jejuni, and the bacterium binds to it. There are no studies on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 50 publications
2
86
0
Order By: Relevance
“…We believe that such a protective role may be a generalized defense against many enteric bacterial pathogens. Indeed, there have been reports of Muc2 interactions with other enteric pathogens, including Campylobacter jejuni (52) and the attaching and effacing (A/E) pathogen Citrobacter rodentium (53).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that such a protective role may be a generalized defense against many enteric bacterial pathogens. Indeed, there have been reports of Muc2 interactions with other enteric pathogens, including Campylobacter jejuni (52) and the attaching and effacing (A/E) pathogen Citrobacter rodentium (53).…”
Section: Discussionmentioning
confidence: 99%
“…Mucin is a powerful attractant for Brachyspira, Campylobacter and some Vibrio cholerae (Witters & Duhamel, 1999;Tu et al, 2008). Alemka et al (2010) demonstrated that mucus supports C. jejuni reproduction and enhances adhesion to and invasion of the underlying epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Mucin-2 acts as the first barrier invading microorganisms have to overcome and thus plays a pivotal role in colonic protection [37]. However, C. jejuni is able to bind to Mucin-2 [38] and to upregulate mucin-degrading enzymes [39]. The impact of mucins in contributing to resistance to C. jejuni infection is further underlined by the fact that Mucin-deficient mice experience higher intestinal pathogen burden, display more distinct epithelial damage as well as rapidly developing systemic infection upon C. jejuni infection [40].…”
Section: Discussionmentioning
confidence: 99%